2001
DOI: 10.1007/s005860100254
|View full text |Cite
|
Sign up to set email alerts
|

Graf ligament stabilisation: mid- to long-term follow-up

Abstract: IntroductionMechanical instability in the lumbar spine is a term often used to describe an altered pattern of segmental movement causing pain. This is usually due to degenerative disease. Historically, symptoms of mechanical instability have been treated surgically with spinal fusion.In an attempt to modify the movement pattern of an abnormal motion segment, the Graf ligament system was introduced. It consists of modified titanium pedicle screws inter-connected with bands of braided polypropylene. This arrange… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
1
5

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(32 citation statements)
references
References 7 publications
2
24
1
5
Order By: Relevance
“…Rigby et al [ 18] also showed that 41% of their patients were not satisfied with the procedure after a mean followup of 51 months. They cautioned against the continued use of this method.…”
Section: Discussionmentioning
confidence: 97%
“…Rigby et al [ 18] also showed that 41% of their patients were not satisfied with the procedure after a mean followup of 51 months. They cautioned against the continued use of this method.…”
Section: Discussionmentioning
confidence: 97%
“…Some of them (Graf, Dynesys) were secured to the spine by pedicle screw fixation systems [17], while other implants are secured in the interspinous space [38,48]. Although early results of pedicle-screw systems of flexible intervertebral stabilization have been encouraging [17] some longterm results have revealed possible drawbacks [18,54], including increased lumbar lordosis, stretching of the Dacron parts, and malpositioning and loosening of pedicle screws leading to increased re-operation rate.…”
Section: Discussionmentioning
confidence: 99%
“…The overall implant constitutes a ''floating'' system with no permanent fixation in the vertebral bone, which might otherwise expose in the risk of loosening. Mechanical human cadaver studies [48] have shown that Wallis permits a reduction in the mobility of intervertebral segments previously destabilized by discectomy and that it achieves an increase in the rigidity of the destabilized segment beyond normal values. There is no implant for the L5/S1 segment and thus it cannot be used below a L4/L5 fusion [63].…”
Section: Surgical Technique and Wallis Interspinous Implantmentioning
confidence: 99%
See 2 more Smart Citations